Semi‐Rational Engineering of Toluene Dioxygenase from Pseudomonas putida F1 towards Oxyfunctionalization of Bicyclic Aromatics. Issue 21 (27th April 2021) - Wissner, Julian L.; Schelle, Jona T.; Escobedo‐Hinojosa, Wendy; Vogel, Andreas; Hauer, Bernhard
Abstract: Toluene dioxygenase (TDO) from Pseudomonas putida F1 was engineered towards the oxyfunctionalization of bicyclic substrates. Single and double mutant libraries addressing 27 different positions, located at the active site and entrance channel were generated. In total, 176 different variants were tested employing the substrates naphthalene, 1, 2, 3, 4‐tetrahydroquinoline, and 2‐phenylpyridine. Introduced mutations in positions M220, A223 and F366, exhibited major influences in terms of product formation, chemo‐, regio‐ and enantioselectivity. By semi‐rational evolution, we lighted up the TDO capability to convert bulkier substrates than its natural substrate, at unprecedented reported conversions. Thus, the most active TDO variants were applied to biocatalytic oxyfunctionalizations of 1, 2, 3, 4‐tetrahydroquinoline, and 2‐phenylpyridine, enabling the production of substantial amounts of (+)‐( R )‐1, 2, 3, 4‐tetrahydroquinoline‐4‐ol (71% isolated yield, 94% ee ) and (+)‐(1 S, 2 R )‐3‐(pyridin‐2‐yl)cyclohexa‐3, 5‐diene‐1, 2‐diol (60% isolated yield, 98% ee ), respectively. Here, we provide a set of novel TDO‐based biocatalysts useful for the preparation of oxyfunctionalized bicyclic scaffolds, which are valuable to perform downstream synthetic processes. Abstract :